Quartile Scores of Scientific Journals: Meaning, Importance and Usage - Ahmet Asan; Ahmet Aslan (Acta Medica Alanya, 2020)
The Q scores of scientific journals are an analytical tool that determines the ranking of journals based on their own scientific group and impact factor. It shows the rankings of the journal within its own group and it is a useful guide for researchers in the selection of the journal, however it should be used with caution in academic career advancement. Quartile scores may vary according to the scientific categories. The Q scores of a journal briefly show the 25% quantile resulting from quartered the number of journals in the area where the journal is placed. The first quartile has the top 25% of the journals and gets the Q1 score and the last quartile gets Q4 score. And so, the second 25% slice takes Q2 score and the third 25% slice takes Q3 score.